Development, Implementation, and Evaluation of Instructional Learning Package in Teaching-Learning Geometry 7 - Sy, Julian John Paul P.; Ambay, Rica Joy C.; Mercado, Justine C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The present study investigated the effectiveness of a developed learning package in teaching Geometry 7 specifically in constructions and solving problems involving polygons. Geometry is one of the subjects that many students find to be the most difficult and may be challenging for some children. The major goal of this study is to determine the effect of the developed learning package in teaching Geometry 7 improving the skills of construction and problem solving skills of the students. The learning package sought to provide an engaging learning environment by merging real-world situations and game-based components. The research design adapted a quasi-experimental design wherein it has a control and an experimental group. Pretest and posttest were conducted in the control and experimental group to compare the performance of students who utilized the learning package with those who did not. With the pretest and posttest scores of the students, it was found that the learning package was not effective in school A but effective in school B. The learning package has had a big impact in rural areas, resulting in the absence of significant differences between rural and urban schools. Furthermore, the study did not produce significant interaction between the locality and the usage of the developed learning package. Thus, the Developed Learning Package improved students’ comprehension and engagement with Geometry.